Karakteristik Mutu Organoleptik Seduhan Bubuk Kopi Robusta (Coffea canephora) Dengan Suhu Penyangraian Yang Berbeda - Ridawati Marpaung; Hayata Hayata; Yuni Putri Ayu (Universitas Batanghari, 2021)
This research is entitled : Organoleptic Quality Characteristics of Robusta Coffee ( Coffea canephora ) Brewing with Different Roasting Temperatures. Implementation treatment and organoleptic tests this research at the Faculty of Agriculture UNBARI Jambi in March-August 2021 . The environmental design used in this study was a completely randomized design. The treatment design consisted of different roasting temperatures, with 4 levels of roasting temperature, as follows: p1 = roasted at 180 0 C ; p 2 = roasted with a temperature of 2000 C ; p 3 = roasted at a temperature of 220 0 C and p 4 = roasted at a temperature of 240 0 C . Each treatment was repeated 3 times so that there were 12 experimental units .The observed variables of steeping coffee grounds in this research were : color, aroma, taste, bitterness, pH and water content of coffee grounds. To see the effect of different roasting temperatures, statistical analysis was carried out: the variables of color, aroma, taste, bitterness, and preference were carried out by a perception test with a 5-scale Likert scale then tabulated the data, followed by analysis of variance, then continued with the DNMRT test at level 5 %. While testing the pH and moisture content of coffee grounds was analysis of variance and further test of DNMRT at the level of 5%. Roasting coffee beans at a temperature of 240 0 C, resulted in the highest organoleptic assessment of brewing coffee grounds in terms of color, aroma, taste, bitterness, preference, pH, and water content.